影响北极地区迅速变化的一些关键过程研究 - 陈立奇; 赵进平; 卞林根; 陈波; 陈敏; 高爱国; 高众勇 (2003)
最近研究证明 ,近半个世纪来 ,北极地区正在发生迅速变化。部分地区温度上升了 2— 3°C ,北冰洋海冰退缩 5 %,中心地区海冰厚度变薄 ,海面压力降低 ,中上层水淡化和变暖 ,吸收CO2 能力增加 ,臭氧耗损和紫外线辐射增强。中国于 1 999年开展了“中国首次北极科学考察” ,在楚科奇海、加拿大海盆、白令海以及临近海域开展了海冰气相互作用的多学科综合考察 ,对北极的区域特征及其在全球变化中的作用研究获得一些新的认识。观测到加拿大海盆中层水持续增暖的现象 ,揭示了西北冰洋与白令海水体交换的途径和次表层暖水结构 ,发现了加拿大海盆是北冰洋河水的主要储存区。利用联合冰站观测数据 ,模拟了北冰洋夏季大气边界层结构和下垫面能量平衡的变化特征 ,定量给出了北冰洋夏季海 /气和冰 /气之间湍流通量和边界层参数的差异。海 /气CO2 的通量观测表明 ,考察区的大部分海域均为大气CO2 汇区 ;西北冰洋海冰区具有较高的生物泵运转效率 ,楚科奇海陆架是一个高效的有机碳“汇”区 ,寒冷水体中微生物活动并未受到明显抑制。沉积物的地球化学过程研究表明 ,海底表层沉积物中碘含量存在着由低纬度到高纬度增加趋势 ,北极地区可能是碘的汇区 ,碘可作为极区古海洋中的地球化学元素变化的重要指标。楚科奇海、白令海? Recent evidences show that a rapid change has occurred in the Arctic since the last half century. Temperature increased 2-3 °C in some regions of the Arctic continents. Coverage of sea ice decreased 5% in the Arctic Ocean, thickness of sea ice shrunk in the center of the Arctic Ocean, the surface and intermediate water layers are freshening and warming, absorption of the atmospheric CO 2 increased in the marginal sea ice zone, and depletion of ozone appeared and ultraviolet radiation increased. To understand processes of air sea ice interaction and their impacts to global change, First Chinese National Arctic Research Expedition was conducted from July 1 to September 9 of 1999 to implement a multidisciplinary survey in the Chukchi Sea, the Canada Abyssal Plain, and the Bering Sea. Advancement has achieved to understand regional characteristics of the Arctic and the sub Arctic as well as their effective processes on global change. A phenomenon of persistent warming has been observed in the medial layer waters in the Canada Abyssal Plain where has also been found as a major sink of fresh water from rivers to the Arctic Ocean. Exchange of water masses between the western Arctic Ocean and the Bering Sea as well as warm water structure in secondary surface layers were studied. Using data from multidisciplinary investigations on a floating packed ice, the atmospheric boundary layer was characterized, variations of energy balance on the underlying surface were modeled, and as air sea and ice air turbulent fluxes were calculated respectively, as well as differences of their parameters in the boundary layer were discussed. Fluxes of air sea CO 2 showed that most of the surveyed waters would play as a sink of the atmospheric CO 2. Higher biological pump operations presented in the western Arctic Ocean with an effective organic carbon sink in the Chukchi Sea. Microbiological activities didn′t find remarkably suppressed even in the cold waters. Biological processes of iodine in the surveyed sediment cores indicated a trend of concentration distribution increases from low to high latitude, suggesting a potential sink of iodine in the Arctic region and implying iodine as a significant indicator for variations of paleooceanic geochemical elements in the polar regions. There was a diversity of community and a variety of ecological structure in the Chukchi Sea or the Bering Sea, but a higher nutrient and low chlorophyll (HNLC) appeared in the Bering Abyssal Basin and lower levels of primary production and particle organic matters occurred in summer sea ice melting season in the Chukchi Sea. Pb in marine aerosols over the Chukchi Sea showed a high concentration. Ozone concentrations in the surface air or their daily change magnitude decreased with increase of latitude, which could be attributed to impacts from climate system such as from a warm high passed or a change of the tropopause height. 中国首次北极科学考察和国家自然科学基金 ( 4 0 2 760 0 1 )资助